Copepod vertical diel migration on the continental shelf of South Central Vietnam - Tam Vinh, Nguyen; Duyen Ngoc, Huynh Thi; Nhu Hai, Doan (Academia Journal of Biology, 2023)
Zooplankton often migrates within the water column for different purposes but mostly to find food and avoid predators. Vertical migration over 24 hours is called diel vertical migration (DVM). However, knowledge of DVM for different zooplankton species is limited. The present study analysized DVM based on species distribution in the water column at each different times of day at two stations on the central Vietnam shelf. One station was on the shelf (LT2) and another was on the shelf slope (FK002). The results showed that 69 zooplankton species, out of 191 recorded at the two stations, having strong DVM (dz > 15 m). Among them, 38 species were nocturnal and 36 species showed reverse DVM. Species with nocturnal DVM were less on the shelf station than on the shelf slope. Moreover, detailed analysis at LT2 showed 18 species having DVM at dawn and 13 species having DVM at sunrise. This study provides important data for zooplankton ecology in Vietnam and marine tropical waters.